Influence of aquatic plants on the predation of Piaractus mesopotamicus larvae by Pantala flavescens - doi: 10.4025/actascibiolsci.v32i2.5167 - Carlos Henrique Figueiredo Lacerda; Carmino Hayashi; Claudemir Martins Soares; Carlos Eduardo Bento Fernandes (Acta Scientiarum. Biological Sciences, 2010)
The experiment aimed to study the influence of the aquatic plants E. najas, P. stratiotes and S. auriculata on the predation of P. mesopotamicus larvae by P. flavescens. One hundred and twenty larvae of P. mesopotamicus and 24 larvae of P. flavescens were placed in 24 aquariums with capacity of 12 L, with one Odonate per aquarium. Treatments were different regarding the species of aquatic plants E. najas, S. auriculata and P. stratiotes, with one control treatment without aquatic plants. One aquarium (12 L) containing one Odonate and 30 P. mesopotamicus larvae was considered one experimental unit. After 18 hours, the Odonates were removed from the aquariums and fish larvae left (alive) were counted in each experimental unit. The survival rate of P. mesopotamicus larvae in the treatment without aquatic plants (control) was significantly lower than in the treatment with E. najas. However, the survival rates in the aquariums with floating aquatic plants did not differ from the control. The morphological characteristics of E. najas promoted higher structural complexity in the environment, offering more protection to the fish larvae, and increasing their survival. We concluded that the presence of the submerged aquatic plant E. najas promoted the reduction of predation of P. mesopotamicus larvae by Pantala flavescens. Larvae; Piaractus mesopotamicus; Pantala flavescens; predation; aquatic plants